Reclamation and Management of Alkali Soils -A Decision Support System - Satvinder Singh,; Satwinder Singh,; O P Singh,; S K Adlakha,; Harnam Sikarwar,; Tauqueer Ahmad, (Journal of Soil and Water Conservation, 2022)
A decision support system was developed for reclamation and management of alkali soils. The programming of the decision support system was done in Visual Basic having data inter-linkage with MS Excel and MS Access. The decision support system identified different reclamation and management techniques as land levelling, gypsum requirement and its addition, cultivation of tolerant crops, cultural practices, afforestation, groundwater recharge, round water use and surface drainage. It also incorporated the concept of thin and frequent irrigations for irrigating alkali soils. The decision support system provided design of all irrigation methods for alkali soils except sprinkler irrigation, as it was found unsuitable. To reclaim saline-alkali soils, the decision support system uses leaching as the first step followed by adoption of reclamation techniques same as that for alkali soils.